2016
DOI: 10.1016/j.immuni.2016.01.021
|View full text |Cite|
|
Sign up to set email alerts
|

Distinct Signaling of Coreceptors Regulates Specific Metabolism Pathways and Impacts Memory Development in CAR T Cells

Abstract: Chimeric antigen receptors (CARs) redirect T cell cytotoxicity against cancer cells, providing a promising approach to cancer immunotherapy. Despite extensive clinical use, the attributes of CAR co-stimulatory domains that impact persistence and resistance to exhaustion of CAR-T cells remain largely undefined. Here, we report the influence of signaling domains of coreceptors CD28 and 4-1BB on the metabolic characteristics of human CAR T cells. Inclusion of 4-1BB in the CAR architecture promoted the outgrowth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
620
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 936 publications
(691 citation statements)
references
References 53 publications
33
620
2
2
Order By: Relevance
“…This could reflect an advantage of CD137 in inducing mitochondrial respiration, in addition to glycolysis. This is consistent with previous observations comparing the cytoplasmic tails of CD28 and CD137 in CARs (19). CD28 plus CD137 dual costimulation further increased Mitotracker content (Fig.…”
Section: Experiments Human Cd8supporting
confidence: 93%
See 3 more Smart Citations
“…This could reflect an advantage of CD137 in inducing mitochondrial respiration, in addition to glycolysis. This is consistent with previous observations comparing the cytoplasmic tails of CD28 and CD137 in CARs (19). CD28 plus CD137 dual costimulation further increased Mitotracker content (Fig.…”
Section: Experiments Human Cd8supporting
confidence: 93%
“…In this regard, a CD137-containing CAR did not increase glycolysis (19), perhaps suggesting differences between the chimeric and naturally occurring molecules.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Using mRNA electroporation, Kawalekar et al (2016) demonstrated that the enhanced survival of 41BBζ CAR T cells is associated with an increased frequency of CD8+ T CM cells, while CD28ζ CAR T cells exhibited effector memory differentiation (T EM ), leading to limited persistence. (Kawalekar et al 2016).…”
Section: How To Improve Car T-cell Efficacy and Increase Access To Pementioning
confidence: 99%